Devices for the transport and microbiological detection of Neisseria gonorrhoeae in sexual health clinic samples: a prospective comparative study. (March 2023) - Jonker, Leon; Phillips, Matt
Background: Propagation and microbiological detection of N. gonorrhoeae can be challenging due to the fastidious nature of the bacterium outside the human host environment. Different sample transport options were evaluated in order to address this issue. Methods: Symptomatic and high-risk patients consented to take part. Standard practice in clinics involve using a guanine and cytosine selective (GC) plate for transport and incubation. Other devices were assessed in two different studies. MWE's Sigma VCM™-a transport device for use between clinic and laboratory-was used in one study ( n = 166). In the other, ( n = 102), Biomed's Intray™ plates were used, which can be used for both initial transport and incubation at the destination laboratory. Results: In the Sigma VCM™ study, positive results were obtained for 14% (Sigma VCM™), 21% (GC plates); the distribution of outcomes did not significantly differ between the two microbiological sampling methods ( p -value 0.09, Chi-squared test). Concerning the InTray™ sub-study, N. gonorrhoeae was detected in 9% (InTray™), 13% (GC plating) of cases respectively, with again no significant difference between the microbiological sampling methods ( p -value 0.25). Regression analysis identified a significant association between N. gonorrhoeae detection and male patients, absence of dysuria and previous gonorrhoea infection. Conclusion: No significant difference in rate of microbiological detection of N. gonorrhoeae could be detected between different transport devices in a sexual health clinic setting. Performance appraisal of transport devices for bacterial sexually transmitted infection can inform practitioners' options regarding said devices.